Processing by local interneurons of mechanosensory signals involved in a leg reflex of the locust - Burrows, M (J Neurosci, 1986)
At the distal end of the tibia of a locust hind leg are 2 pairs of movable spurs that can be moved by contact with external objects--as, for example, when the body sways from side to side and loads one leg unevenly or when the foot is placed on rough ground--but not by direct muscular action. Movements imposed on a spur evoke phasic bursts of spikes in the axon of a single receptor cell at its base. If the displacement is maintained, however, the response adapts within a few seconds. The afferents from these spur receptors excite particular spiking local interneurons with cell bodies at the ventral midline of the metathoracic ganglion. Each afferent spike is consistently followed at a constant latency by a depolarizing potential in one of these interneurons. The potential can evoke a spike, and its amplitude is enhanced by a hyperpolarization applied to the interneuron. The central delay to this chemically mediated EPSP, which also includes conduction time to synaptic sites, probably indicates a direct connection. Some spiking local interneurons are excited by the 2 anterior spurs but are unaffected by the 2 posterior ones, while others receive the converse pattern of inputs. The receptive fields of these interneurons also include regions on either the anterior or posterior surfaces of the tibia with excitatory inputs from hair afferents. A reliable inhibitory reflex effect on the single levator tarsi is evoked by movement of any of the 4 spurs. The inhibitory potentials are not caused directly by the sensory afferents but involve the spiking local interneurons upon which the afferents synapse. The receptive field of this motor neuron therefore results from the convergence of inputs from a few interneurons. Motor neurons of other tarsal muscles are unaffected by movement of the spurs, but those of some more proximal muscles may be excited. These reflex effects should enhance the traction of the tarsus with the ground.